Changing paradigms: a historical analysis of school autonomy and accountability policies in Colombia - Tomás Esper (Taylor & Francis Group, 2024)
Spreading like wildfire, school autonomy with accountability (SAWA) policies have transformed education worldwide. Rooted in new public management, SAWA is a 'policy bundle' that links greater decision-making at the school level with standardization and monitoring practices like large-scale assessments and performance indicators. As with every traveling reform, SAWA varies among countries influenced by prior policies, the government's ideology, and stakeholders' interests. However, studies often focus on individual elements of the SAWA bundle rather than the complete package. Thus, this paper addresses this gap by analyzing SAWA in Colombia, examining how policy paradigms and institutional legacies have shaped its trajectory - from its adoption to the present. Data combines policy document analysis and interviews with key informants (n = 48). The study shows the 1991-1994 reform period as a critical juncture in Colombia, consolidating a decentralized governance system dominated by a democratic educational paradigm. However, a counter-reform in 2001 produced significant effects under an opposing sign. Eager to recentralize educational political and administrative control, Colombia's national elites incrementally deployed large-scale assessments, learning standards, and system-wide performance monitoring policies configuring a 'quality assurance' SAWA model. While market-like policies incentivizing competition and high-stakes were rapidly abandoned, SAWA policies represent a managerial turn in Colombia's education.